Increasing the proportion of healthier foods available with and without reducing portion sizes and energy purchased in worksite cafeterias: protocol for a stepped-wedge randomised controlled trial - James P. Reynolds; Daina Kosīte; Brier Rigby Dames; Laura A. Brocklebank; Mark Pilling; Rachel Pechey; Gareth J. Hollands; Theresa M. Marteau (BMC, 2019)
Abstract Background Overconsumption of energy from food contributes to high rates of overweight and obesity in many populations. A promising set of interventions tested in pilot studies in worksite cafeterias, suggests energy intake may be reduced by increasing the proportion of healthier - i.e. lower energy - food options available, and decreasing portion sizes. The current study aims to assess the impact on energy purchased of i. increasing the proportion of lower energy options available; ii. combining this with reducing portion sizes, in a full trial. Methods A stepped-wedge randomised controlled trial in 19 worksite cafeterias, where the proportion of lower energy options available in targeted food categories (including main meals, snacks, and cold drinks) will be increased; and combined with reduced portion sizes. The primary outcome is total energy (kcal) purchased from targeted food categories using a pooled estimate across all sites. Follow-up analyses will test whether the impact on energy purchased varies according to the extent of intervention implementation. Discussion This study will provide the most reliable estimate to date of the effect sizes of two promising interventions for reducing energy purchased in worksite cafeterias. Trial registration The study was prospectively registered on ISRCTN (date: 24.05.19; TRN: ISRCTN87225572; doi: https://doi.org/10.1186/ISRCTN87225572).